Testing the third-person effects theory on political campaign in Malaysia - Syed Abdullah Idid, Syed Arabi; Wok, Saodah (2010)
This paper tests the use of Third-Person Effect Theory (TPET) on political campaign on self, family, supporters, non-supporters, and non-supporters of other parties. Previous research mainly tested the TPET on the mass media. Thus, the application of the TPET is extended to gauge the effect of political campaign. This is important as the campaign can have a great influence on those who are the target of the campaign. The study tries to find out the effects of campaign as a vehicle in mobilizing the audience on the voting outcome of the political campaign. The study was conducted nationwide involving 1654 respondents. Data were collected using an interview schedule. Data were analyzed for its descriptive and inferential statistics to answer the objectives of the study and to test the hypotheses of the study. Findings show that, on the whole, the respondents think that the political campaigns are able to influence the party supporters, whether they belong to the reigning party or the opposition party. In addition, the respondents who are supporters of the ruling party said that they and their families are very much influenced by BN political campaign. The supporters of the opposition also have similar perception of their own party. Therefore, the Third-Person Effect Theory holds true for the study on political campaign effects.